2015
DOI: 10.1021/jacs.5b05561
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Ligand-Centered Electrocatalytic Hydrogen Evolution and Hydrogen Oxidation at a Noninnocent Mononuclear Metal–Thiolate

Abstract: The noninnocent coordinatively saturated mononuclear metal-thiolate complex ReL3 (L = diphenylphosphinobenzenethiolate) serves as an electrocatalyst for hydrogen evolution or hydrogen oxidation dependent on the presence of acid or base and the applied potential. ReL3 reduces acids to H2 in dichloromethane with an overpotential of 380 mV and a turnover frequency of 32 ± 3 s(-1). The rate law displays a second-order dependence on acid concentration and a first-order dependence on catalyst concentration with an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 40 publications
2
95
0
Order By: Relevance
“…The inverse value of KIE ( k H / k D < 1) value is consistent with a metal hydride intermediate based on previous reports by Gray and Fukuzumi , . In contrast, the inverse KIE for 1 is distinct from the value of 10 observed for Re(L 1 ) 3 , which operates via ligand centered HER , . In the strong acid HCl, an increased TOF of 140 s –1 is observed.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The inverse value of KIE ( k H / k D < 1) value is consistent with a metal hydride intermediate based on previous reports by Gray and Fukuzumi , . In contrast, the inverse KIE for 1 is distinct from the value of 10 observed for Re(L 1 ) 3 , which operates via ligand centered HER , . In the strong acid HCl, an increased TOF of 140 s –1 is observed.…”
Section: Resultssupporting
confidence: 89%
“…For the nickel complex 1 , the HER TOF with acetic acid or HCl is similar to that reported for Re(L 1 ) 3 , although the latter operates at a lower overpotential. Despite similar activities, the mechanisms of the Ni and Re systems are different as reflected in the inverse KIE of 0.82 measured for 1 as compared to the KIE of 10 for Re(L 1 ) 3 . This is further observed in the HOR results.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…9 Electrochemical studies show that reported heterogeneous H 2 evolution from MoS 2 proposing exposed unsaturated S edge atoms as reaction sites. 172 The unique reactivity of ReL 3 could be attributed to a sterically crowded, kinetically inert, and coordinativley saturated metal center that prevents facile formation of metal hydride, which is proposed for other active metal−sulfur catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The work described in Chapter Four was supported in part by the National Science 192 has expanded the realm of HER electrocatalysts beyond traditional transition metalhydrides to include non-transition metal, 76,99 and metal-free catalysts 76 for HER invoking ligand-directed radical coupling of H-atoms 77,193 or protonation of ligand-centered hydrides. 71,76 As discussed previously in Chapter Four, we reported the first examples of HER/HOR activity with the non-innocent bis(thiosemicarbazone) ligand framework.…”
Section: Acknowledgementmentioning
confidence: 99%